THE ANALYSIS OF PRAGMATIC DEIXIS REALIZED ON BIG HERO MOVIE 6 - Ade Apriyana (Universitas Galuh, 2021)
This paper attempted to analyze the pragmatic deixis realized in Big Hero movie 6. The objectives of the study aims to investigate the realization of the kinds of pragmatic deixis and the dominant kinds of pragmatics deixis realize in Big Hero movie 6. The data were obtained through the use of content analysis. A descriptive study was employed in analysing the data from the script of the movie.). In this study, the writer addressed two research questions: (1) what are kind of deixis realized in the utterances in Big Hero movie 6? (2) what are kind of dominant deixis used by the characters in Big Hero movie 6? The descriptive statistic of percentage was used to calculate the result of pragmatic deixis realized in Big Hero movie 6. Based on the process of pragmatic deixis, it found that there were five kinds of pragmatics deixis realized in Big Hero Movie 6. They were person deixis, time deixis, place deixis, social deixis, and discourse deixis. After analyzing the data, the dominant kinds of pramatic deixis frequently used in the script of Big Hero movie 6 was second person deixis. It realized 46% of total 10 scenes from total 25 secenes which were analysed. Based on those findings, the writer recommends that this study can be used as one of reference in learning linguistics study and determining the meaning of the context. Keywords: Pragmatic Deixis, Big Hero Movie 6